Temerloh Parliamentary Consultative Council (TPCC) as a model of participatory/deliberative democracy in Malaysia - Mohd Sani, Mohd Azizuddin; Omar, Rusdi; Abdullah, Mohamad Ainuddin Iskandar Lee; Mukhtaruddin, Mas Juliana; Abdullah, Ahmad Amir (2012)
This paper is an attempt to analyse a shift in decision making approach for Malaysia's public policy formulation. Since the 12th general election, people participation in decision-making process is becoming very important in order for the government to produce a people friendly public policy.Therefore, this paper takes the opportunity to study a model of participatory or deliberative democracy which has been introduced through the Temerloh Parliamentary Consultative Council (TPCC) by Deputy Minister of Ministry of Higher Education, Dato' Saifuddin Abdullah. Model that has been introduced by Dato' Saifuddin is one of its kinds, which has never been practiced before or in the government's agenda for effective governance. Researchers are in the intention to analyse the effectiveness and the TPCC model can be the best model of public deliberation in Malaysia and can be copied by other constituency as well.